Associations of the miRNA-146a rs2910164 and the miRNA-499a rs3746444 Polymorphisms With Plasma Lipid Levels: A Meta-Analysis - Liu, Fuqiang; Wang, Shengping; Luo, Zhi (Frontiers in Genetics, 2021)
Background: The studies of miRNAs are vibrant and remain at the forefront in the cardiovascular system. Emerging studies indicate that the genetic polymorphisms of the miRNA gene may affect lipid metabolism; this study aims to clarify the specific correlations between the rs2910164 and rs3746444 polymorphisms and lipid levels. Methods and Results: A comprehensive search of literature was performed from December 31, 2020, to May 31, 2021, by searching of the PubMed and the Cochrane databases. The standardized mean difference (SMD) and 95% confidence interval (CI) were used to evaluate the differences in lipid levels between the genotypes. rs2910164, a functional polymorphism in the miRNA-146a gene, was associated with increased triglycerides (TG) (SMD = 0.35, 95% CI = 0.15–0.54, p < 0.001), total cholesterol (TC) (SMD = 0.43, 95% CI = 0.16–0.70, p < 0.001), and low-density lipoprotein cholesterol (LDL-C) (SMD = 0.37, 95% CI = 0.11–0.63, p = 0.01) as well as decreased high-density lipoprotein cholesterol (HDL-C) (SMD = −0.27, 95% CI = −0.47−0.07, p = 0.01) levels. rs3746444, a functional polymorphism in the miRNA-499a gene, was only correlated with decreased TG (SMD = −0.09, 95% CI = −0.17−0.01, P = 0.03) levels. Conclusions: The miRNA-146a rs2910164 polymorphism is significantly associated with atherogenic dyslipidemia.